IMPLEMENTASI STOP KONTAK PINTAR PADA LAMPU TAMAN DENGAN MENGGUNAKAN MIKROKONTROLLER WEMOS D1 R1 BERBASIS IOT: Indonesia - Harun Sujadi; Tantri Wahyuni (Universitas Majalengka, 2021)
The socket is an electrical installation that functions as a liaison between electric current and electrical equipment, one example is a garden lamp. To be able to turn on, you need a power outlet, but manual sockets are considered less effective due to the development of human habits leaving the house with the lights still on. With current technological developments, namely utilizing internet of things (IoT) technology, a smart socket is made that can be controlled remotely via a smartphone. The smart socket is made using Wemos D1 R1 as the microcontroller and is equipped with a raindrop sensor as a safety where the system will turn off the electricity automatically when the sensor detects water and a notification will appear on the smartphone as if water has been detected, so users don't have to worry about leaving the house. with a state of forgetting not to turn off the garden lights.